Features of uterine blood flow in adolescents with abnormal uterine bleeding of puberty - Irina Tuchkina; Lyudmila Vygovskaya; Anastasia Novikova (National Scientific Medical Center, 2019)
The aim of this study was to study the ultrasound characteristics of the pelvic organs and the characteristics of uterine blood flow in adolescents with abnormal uterine bleeding during puberty. Methods: Investigate 93 adolescent girls with abnormal uterine bleeding during puberty (AUBDP), aged 11 to 18 years (mean age was 14.5 ± 3.5 years). Patients with AUBDP were divided into 2 clinical groups: I group consisted of 44 patients 11-14 years old, group II - 49 adolescent girls 15-17 years old. The control group included 25 person of the same age without menstrual disorders. The frequency of relapses of AMKPP in group I was 20,4%, in group II - 28,5%. Ultrasound and Doppler study was performed using an ultrasound scanner "Siemens" (Germany), using a transabdominal sensor (3.5 MHz) and a transvaginal sensor (6.5-7 MHz) in adolescents who have sex. The conditional of blood flow in the uterine and spiral arteries was performed using Doppler study. The indices of vascular resistance in both the uterine and spiral arteries, the index resistance (IR), the pulsation index (PI), and the systolic-diastolic ratio (S/D) were calculated. Results: The study revealed hemodynamic changes in blood flow in girls with AUBDP. In this connection, the described changes in the parameters of blood flow in a. uterinae and a. radialis can serve as an additional diagnostic criterion for determining the risk of uterine bleeding during puberty. Conclusion: Based on the study, ultrasound and Dopplerometric features of the pelvic organs in adolescent girls with AUBDP were found, which were characterized by an increase in the size of the uterus, heterogeneous endometrial echostructure, an increase in the size of the ovaries, an increase in systolic and diastolic blood flow rates, and vascular resistance indices in a. uterinae and a. radialis